2021
DOI: 10.1111/jpc.15535
|View full text |Cite
|
Sign up to set email alerts
|

Emergency mental health presentations in children with autism spectrum disorder and attention deficit hyperactivity disorder

Abstract: Aim To characterise the key features and management of young people presenting to the emergency department (ED) with a mental health (MH) complaint and a known diagnosis of autism spectrum disorder (ASD) or attention deficit hyperactivity disorder (ADHD). Methods Retrospective review of all ED MH presentations in children aged 7–17 years, presenting over a 12‐month period from the 1st of January 2018 to the 31st of December 2018, to the Royal Children's Hospital in Melbourne, Australia. Univariate analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…autism spectrum disorder (ASD) are over-represented. 12 There is also a strong female preponderance, whereas in adult ASBD the majority are male. 10,11,13 A step-wise approach is endorsed for the management of these young people.…”
Section: Key Findingsmentioning
confidence: 99%
“…autism spectrum disorder (ASD) are over-represented. 12 There is also a strong female preponderance, whereas in adult ASBD the majority are male. 10,11,13 A step-wise approach is endorsed for the management of these young people.…”
Section: Key Findingsmentioning
confidence: 99%
“…For some young people, self‐harming behaviours necessitating emergent care may actually represent a first presentation of a previously undiagnosed neurodevelopmental condition 24 . A retrospective review from the Royal Children's Hospital Melbourne found that young people with a diagnosis of ASD and/or ADHD make up a quarter of mental health presentations to ED, with the most common complaint being acute severe behavioural disturbance 25 . These findings highlight the need for emergency clinicians to have a sound knowledge base and understanding of these conditions and appropriate management approaches.…”
Section: Prevalence and Ed Usementioning
confidence: 99%
“…Studies from the USA, Australia and Canada have found that children and adolescents with autism represent a high proportion of the total mental health (MH) emergency department (ED) presentations in this age group, with high rates of repeat and after-hours presentations 10–13. This includes for severe acute behavioural disturbance, self-injurious behaviour and aggression.…”
Section: Introductionmentioning
confidence: 99%
“…This can cause increased patient distress, worsening behaviour and safety risks. Children with autism and/or ID who present with MH complaints and BOC are more likely to require complex management including involvement of an acute crisis team (an inpatient multidisciplinary team activated to de-escalate high risk behaviours), physical or chemical restraint 10 13…”
Section: Introductionmentioning
confidence: 99%